Tension - torsion fatigue tests on the proton exchange membrane Nafion 115 (Perfluorosulfonic acid) - Gonzalo Mariano DOMINGUEZ ALMARAZ; Luis M. TORRES DUARTE; Christian J. TORRES PACHECO (Fracture and Structural Integrity)
Biaxial tension-torsion fatigue tests are carried out on the membrane material Nafion 115 (perfluorosulfonic acid, PFSA). This polymeric material is used in fuel cells as proton exchange membrane, undergoing frequently mechanical loading of tension and torsion during its industrial life. In order to carry out the fatigue tests on this polymeric material a self-designed  and self-constructed machine was used, working under the following conditions: from 0 to 50 degrees of torsion, 0 to 60 MPa of initial tensile stresses, from room temperature (22 to 25° C) to 80° C, and two values for relative humidity: environmental and saturated relative humidity. All fatigue tests were carried out at the frequency of 1.2 Hz. This paper presents the first results, which concerns the following testing conditions: constant torsion angle of 50 degrees, 5 initial tensile stress of 60, 55, 50, 45 and 40 MPa, room temperature (22-25° C) and environmental humidity (50 – 60 %). The experimental results show that fatigue endurance decreases noticeably when the tensile stress increases. In the final section are presented the fracture surfaces observed by SEM, in order to investigate the principal trends of crack initiation and propagation under this modality of biaxial fatigue loading.